Numerical investigation of initiation and propagation of hydraulic fracture using the coupled Bonded Particle–Lattice Boltzmann Method. (March 2017) - Wang, Min; Feng, Y.T.; Wang, C.Y.
Highlights: It presents a novel coupled technique for the simulation of fluid–solid interactions in hydraulic fracturing. The microscopic method can process fluid–particle interactions at the grain-level with high accuracy. BPLBM can reproduce the onset and propagation of hydraulic fracture without complicated damage criteria. BPLBM is natural to parallel due to local fluid–solid interactions and explicit time-stepping scheme. Abstract: This paper presents a coupled Bonded Particle and Lattice Boltzmann Method (BPLBM) for modelling fluid–solid interactions in engineering, e.g. geomechanics. In this novel technique, the Bonded Particle model is employed to describe the inter-particle interactions, and the bonds between contacted particles are assumed to be broken when the tensional force and/or tangential force reach a certain critical value; while the Lattice Boltzmann method is used to model the fluid phase, and the Immersed Moving Boundary (IMB) scheme is utilised to resolve the fluid–solid interactions. Based on this novel technique, the investigation of hydraulic fracturing is carried out. The onset and propagation of hydraulic fracture are successfully captured and reproduced. Numerical results show that the coupled BPLBM is promising and efficient in handling complicated fluid–solid interactions at the grain level in hydraulic fracturing.